Potential Effect of Human Platelet Lysate on in vitro Expansion of Human Corneal Endothelial Cells Compared with Y-27632 ROCK Inhibitor - Mohammad Amir Mishan; Sahar Balagholi; Tahereh Chamani; Sepehr Feizi; Zahra-Soheila Soheili; Mozhgan Rezaei Kanavi (Journal of Ophthalmic & Vision Research)
Abstract Purpose: Corneal endothelial cell (CEC) therapy can be used as a promising therapeutic option for patients with various corneal endothelial dysfunctions. In this study, we compared the proliferative effect of human platelet lysate (HPL), as a xeno-free medium supplement, with Y-27632 Rho/rho-associated protein kinase (ROCK) inhibitor, as a well-known proliferative and adhesive agent for CECs, and fetal bovine serum (FBS) as the control, in the culture medium of human corneal endothelial cells (HCECs). Methods: We isolated HCECs from human donors and treated the cells as three different treatment groups including 20% HPL only, 10 μM Y-27632 ROCK inhibitor, combination of 20% HPL and 10 μM Y-27632 ROCK inhibitor, and 20% FBS as the control group. ELISA cell proliferation assay and cell counting was performed on the treated cells. Finally, HCECs were characterized by morphology and immunocytochemistry (ICC). Results: There was no significant proliferative effect of HPL on cell proliferation compared with the cells treated with Y-27632 ROCK inhibitor or the combination of HPL and Y-27632 ROCK inhibitor, but all the respected treatments had significant inducible effect on cell proliferation as compared with FBS-treated cells. The cells grown in all three treatment groups exhibited CEC morphology. Also, there was a higher expression of Na+/K+-ATPase and ZO-1, as CEC characteristic markers, in the culture of HCECs treated with HPL as compared with FBS. Conclusion: HPL offers a xeno - free and affordable medium supplement for CEC expansion that can be used in clinical applications.